2011
DOI: 10.1007/s00264-010-1195-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of dynamic impact testing, histopathology and visual macroscopic assessment in human osteoarthritic cartilage

Abstract: Only ∆E correlated with the condition of the cartilage--the value increased with decreasing quality-and is the most suitable characteristic. This change appears substantial in initial stages of cartilage deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
1
1
1
Order By: Relevance
“…Using the creep test on articular cartilage, Kleeman et al reported a reduction in Young’s modulus with progressive ICRS grade [ 7 ]. However, neither the stress-relaxation test (in the present analysis) nor the dynamic impact test reported by Kos et al [ 27 ] observed a significant difference in Young’s modulus between ICRS grades I and II.…”
Section: Discussioncontrasting
confidence: 84%
“…Using the creep test on articular cartilage, Kleeman et al reported a reduction in Young’s modulus with progressive ICRS grade [ 7 ]. However, neither the stress-relaxation test (in the present analysis) nor the dynamic impact test reported by Kos et al [ 27 ] observed a significant difference in Young’s modulus between ICRS grades I and II.…”
Section: Discussioncontrasting
confidence: 84%
“…Zu deren systematischer Beantwortung belasten Forscher*innen Knorpelgewebe, in vivo oder in vitro, durch einen einzelnen tatsächlichen Stoß mit einem parabolischen oder zylindrischen Gegenkörper von gegebener kinetischer Energie, die durch eine gespannte Feder [106] oder eine Fallgewichts-Apparatur [23] Es stellt sich die Frage, welche (einfachen) mechanischen Größen zur Charakterisierung der aus der stoßartigen Belastung folgenden Gewebeschädigung notwendig oder hinreichend sind. Eine schon längere Tradition hat dabei die Hypothese, dass die (vor dem Stoß vorhandene oder in der Kollision dissipierte) Energie am höchsten mit der Schädigung korreliert 21 [104,105]. So genügt ein einzelner Stoß mit einer Energie von 0,28 J, um lokal Arthrose-typische Gewebe-Degradierung zu initiieren [106].…”
Section: Anwendungen In Der Medizinunclassified
“…Preparing specimens of soft biological tissues can be challenging 44 and deviations from the ideal specimen geometry may have caused non-uniform load application, thus altering the local stress and strain fields. We counted only microcracks in the center of specimens to minimize the possibility of edge effects.…”
Section: Limitations and Outlookmentioning
confidence: 99%